Nanoparticles of biotite mica as Krishna Vajra Abhraka Bhasma: synthesis and characterization - Wele, Asmita; Sourav, De; Dalvi, Madhuri; Devi, Nandini; Pandit, Vijaya (Journal of Ayurveda and Integrative Medicine, 2021)
<div id="abssec0010" style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"><h3 class="u-h4 u-margin-m-top u-margin-xs-bottom" id="sectitle0015" style="color: rgb(80, 80, 80); margin-top: 24px !important; margin-bottom: 8px !important; font-weight: 400 !important; line-height: 1.4 !important; font-size: 1rem !important;">Background Bio-inorganic <a class="topic-link" href="https://www.sciencedirect.com/topics/medicine-and-dentistry/nanoparticle" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about nanoparticles from ScienceDirect's AI-generated Topic Pages">nanoparticles or <a class="topic-link" href="https://www.sciencedirect.com/topics/medicine-and-dentistry/metal-nanoparticle" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about metal nanoparticles from ScienceDirect's AI-generated Topic Pages">metal nanoparticles are used in medicine for diagnostic and treatment purposes. The <a class="topic-link" href="https://www.sciencedirect.com/topics/medicine-and-dentistry/nanomedicine" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about nanomedicines from ScienceDirect's AI-generated Topic Pages">nanomedicines from traditional Ayurvedic system are termed as bhasma. Rasashastra, the branch of inorganic medicines of <a class="topic-link" href="https://www.sciencedirect.com/topics/medicine-and-dentistry/ayurveda" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about Ayurveda from ScienceDirect's AI-generated Topic Pages">Ayurveda, has documented monographs of metal-mineral bhasmas as potent drugs. However there is lack of scientific analytical data of the end products. <div id="abssec0015" style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"><h3 class="u-h4 u-margin-m-top u-margin-xs-bottom" id="sectitle0020" style="color: rgb(80, 80, 80); margin-top: 24px !important; margin-bottom: 8px !important; font-weight: 400 !important; line-height: 1.4 !important; font-size: 1rem !important;">Objectives Present study was aimed at finding out the morphological, structural, elemental and chemical composition of the Krishna vajra abhraka bhasma (KVB). <div id="abssec0020" style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"><h3 class="u-h4 u-margin-m-top u-margin-xs-bottom" id="sectitle0025" style="color: rgb(80, 80, 80); margin-top: 24px !important; margin-bottom: 8px !important; font-weight: 400 !important; line-height: 1.4 !important; font-size: 1rem !important;">Materials and methods Bhasma of KVB (Biotite Mica) was prepared in our laboratory using biotite mica sheets befitting selection criteria and carrying out further processes with strict SOPs as per AFI. <div id="abssec0025" style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"><h3 class="u-h4 u-margin-m-top u-margin-xs-bottom" id="sectitle0030" style="color: rgb(80, 80, 80); margin-top: 24px !important; margin-bottom: 8px !important; font-weight: 400 !important; line-height: 1.4 !important; font-size: 1rem !important;">Results The bhasma complied with the confirmatory tests from Rasashastra. The physical and physicochemical tests correlate with the results obtained by instrumental analytical methods. SEM revealed square shaped nanoparticles of mean size of 92.3 nm. EDAX showed presence of Si, Mg, O, Fe, Ca, Na, C, K and Al. XRD revealed the crystalline nature of bhasma with mixture of various individual oxides and spinel shape of the crystal. DLS showed that the nanoparticles are unimodal in nature. FTIR and NMR showed the organic functional groups obtained from cow milk and selected herbs, indicating unique bio-inorganic nature of the KVB.